Intelligent Decision Support in Intensive Care Units - Nursing Information Modeling - Santos, Manuel Filipe (2010)
The amount of clinical data that is produced everyday in an intensive care environment makes it difficult and time-consuming for health care professionals to find and analyze the information related to the patients’ clinical condition. Moreover, some of that data is in paper-based nursing records, which aggravates this scenario. Increasing the health care provided to the patients is a concern, hence the initiative to develop an electronic nursing record. As a major goal, it will also integrate the decision support system INTCare, providing the means for a rapid access to the patient’s clinical information. This paper presents a specification of the electronic nursing record in development in Hospital Geral de Santo António, Oporto, Portugal. It is fed by three types of information sources and their integration is possible thanks to AIDA, an Agency for Integration, Diffusion and Archiving of Medical Information, implemented at the hospital.